Price policy induced distortions: Undermining incentives to slaughter stall-fed cattle in urban areas of northern Cameroon - Holtzman, J.S. (International Livestock Centre for Africa, 1988)
Examines urban butchers' procurement and slaughter practices under the distorting influence of retail price controls in northern Cameroon. Analyses the coasts and returns to butchering and retailing at urban markets. Discusses the potential effects of maintaining and relaxing price controls on urban slaughter of stall-fed cattle.